2018
DOI: 10.1051/0004-6361/201833664
|View full text |Cite
|
Sign up to set email alerts
|

Temperature constraints from inversions of synthetic solar optical, UV, and radio spectra

Abstract: Context. High-resolution observations of the solar chromosphere at millimeter wavelengths are now possible with the Atacama Large Millimeter Array (ALMA), bringing with them the promise of tackling many open problems in solar physics. Observations from other ground and space-based telescopes will greatly benefit from coordinated endeavors with ALMA, yet the diagnostic potential of combined optical, ultraviolet and mm observations has remained mostly unassessed. Aims. In this paper we investigate whether mm-wav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Even in the presence of time-dependent hydrogen ionization, inversions with ALMA assuming statistical equilibrium are expected to improve the inferred depth-averaged temperatures because they help to set the chromospheric gradient (da Silva Santos et al 2018). The inclusion of other chromospheric lines such as the H and K lines of Ca ii would likely improve the inference (da Silva Santos et al 2018), and therefore it would be interesting to investigate whether predictions of the mm continuum are improved when visible and UV diagnostics are combined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the presence of time-dependent hydrogen ionization, inversions with ALMA assuming statistical equilibrium are expected to improve the inferred depth-averaged temperatures because they help to set the chromospheric gradient (da Silva Santos et al 2018). The inclusion of other chromospheric lines such as the H and K lines of Ca ii would likely improve the inference (da Silva Santos et al 2018), and therefore it would be interesting to investigate whether predictions of the mm continuum are improved when visible and UV diagnostics are combined.…”
Section: Discussionmentioning
confidence: 99%
“…This led us to the conclusion that perhaps the cool ( 4000 K) temperatures observed with ALMA Band 6, which is expected to probe a range of heights typically within ∼700−1200 km (e.g., Loukitcheva et al 2015;da Silva Santos et al 2018), may allow for the cool CO pockets (or clouds) to form. We investigated the problem of CO formation in the chromosphere using our models constrained by IRIS and ALMA observations.…”
Section: Chromospheric Holesmentioning
confidence: 99%
“…Moreover, when performing inversions of multiple spectral bands, one sometimes needs to weight more one region of interest than others. This was done, for instance, in the recent work of da Silva Santos et al (2018) where the continuum wavelengths observed with ALMA (Wootten & Thompson 2009) were of particular importance.…”
Section: Improving the Inversion Configurationmentioning
confidence: 99%
“…Also, we concluded both publications mentioning that we need to perform additional studies to understand better our capabilities for inferring the atmospheric information from spectropolarimetric observations. In particular, to assess the accuracy of the inferred atmospheric parameters through non-local thermodynamic equilibrium (NLTE) inversions of multiple spectral lines with a different height of formation (see, for instance, the recent studies by da Silva Santos et al 2018;Leenaarts et al 2018). Our target is to pave the road for when chromospheric polarimetric observations are routinely performed in the future.…”
mentioning
confidence: 99%
“…When the considered selection of spectral lines are sensitive to a range of heights from the solar atmosphere, depth-stratified inversions allow for the reconstruction of vertical gradients of these parameters in certain parts of the solar atmosphere. The inclusion of more spectral lines in the inversions usually translates into better depth-resolution and better constrained output models (e.g., da Silva Santos et al 2018;Riethmüller & Solanki 2019;Vissers et al 2019).…”
Section: Introductionmentioning
confidence: 99%